Special Economic Zones and Displacement: Need for an Alternative Model - Gill, Sucha Singh (2007)
This paper argues that some transfer of land presently under agriculture to non- agricultural uses will take place in India whether Special Economic Zones (SEZ) are developed or not. But, the present policy of the government on land acquisition falters on a number of counts including livelihood of the displaced, compensation to the owners and non owners of land, sharing of the rise in value of land in the long run, limited employment for the displaced, poor record of rehabilitation and unacceptable mode and formulae of compensation. By delineating SEZs as foreign territories for governance with non- application of the common laws and judicial system, the workers are deprived of their right to collective bargaining, thus making this model discriminatory in nature by promoting exclusionary growth. Hence, it is socially undesirable. There is a need to work out an alternative model for inclusive growth making people partners in development while invoking their consent for socio-economic change. The glimpse of this alternative can be deciphered from the present debate.